Design and development of USM-ROV I - Zulkifli, Zainal Abidin; Mohamed Yusof, Radzak; Mohd Riza, Arshad (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.